The types and levels of physical activity and sedentary behaviour of Senior Phase learners in Potchefstroom - Johanna C.W. De Vos; Dorita Du Toit; Dané Coetzee (Health SA Gesondheid: Journal of Interdisciplinary Health Sciences, 2016)
Background: Worldwide, the health risks of decreasing physical activity levels and increasing sedentary behaviour among adolescents are a raising concern. Objective: To determine the types and levels of physical activity as well as that of sedentary behaviour of a group Senior Phase learners in South Africa.